Virtual teams for dummies - Powers, Tara (--For dummies., 2018)
Set your virtual team on a path to success In the global marketplace, people can work practically anywhere and anytime. Virtual teams cut across the boundaries of time, space, culture, and sometimes even organizations. Rising costs, global locations, and advances in technology are top reasons why virtual teams have increased by 800 percent over the past 5 years. Packed with solid advice, interviews and case studies from well-known companies who are already using virtual teams in their business model and their lessons learned, Virtual Teams For Dummies provides rock-solid guidance on the essentials for building, leading, and sustaining a highly productive virtual workforce. It helps executives understand key support strategies that lead virtual teams to success and provides practical information and tools to help leaders and their teams bridge the communication gaps created by geographical separation-and achieve peak performance.-Includes research findings based on a year-long study on the effectiveness of virtual teams -Mindset and skill shift for managers from old school traditional team management to virtual team management -Covers the communication and relationship strategies for virtual teams -Examines how the frequency of in-person meetings affects a remote team's success Written by an award-winning leadership expert, this book is your one-stop resource on creating and sustaining a successful virtual team.